Analysis of Thermal Damage in FRP Drilling. (2016) - Sorrentino, L.; Turchetta, S.; Colella, L.; Bellini, C.
Abstract: Among machining operations applied to polymeric composite materials, drilling is the more important one due to the need to implement mechanical couplings, which in most cases are not yet possible using structural adhesives. Such process is very critical because not only it causes the interruption of the fibers continuity, but also it can generate localized thermal shock in the resin, due to the presence of extremely hard and abrasive fibers and to the low thermal conductivity of the resin itself, that limits the heat dissipation. These phenomena are more severe in dry machining process, that are used in aeronautic industry. The poor FRP machinability is manifested in the induced phenomena of delamination, fragmentation and matrix thermal damage that cause negative outcomes, such as the reduction of the material fatigue strength and the consequent decay of long-term performance. The evaluation of such critical issues is possible through indirect analysis, that is through the analysis of some control parameters, such as the process forces and temperatures that assume different values depending on the combination of cutting parameters. Therefore, to acquire useful information for machining optimization is possible through process monitoring: the input data can be analyzed, processed and made available to optimize the process parameters in order to reduce critical issues such as the delamination, the fragmentation and the thermal damage. The present work deals with the problem of damage due to the high temperatures reached during the FRP dry drilling process. The temperature was measured by K type thermocouples positioned in the workpiece, near the hole surface, and it was evaluated as a function of the main process parameters in order to estimate the critical cutting conditions that lead to critical temperature overcoming.